(untitled) (Signifiances (Signifying), 2024)
The purpose of this article is to demonstrate how the environment is responsible for the construction of the lexicon in the acquisition of a foreign language and, in particular, Spanish as FL. Our study focuses on the acquisition of Spanish by Italian learners. It takes into consideration the existence, for these learners, of a unique conceptual system, but with branches for the acquisition of a foreign language that arise, not so much from the conceptual system directly, but from the L1. We who are not native speakers can come into contact with our lexicon through the experience we have had with the L1. Whoever learns an L2, especially at an A1-A2 level, looks for expressions in his L1 to translate them into the L2 through their mental construction, while a native will extract the information directly, concretizing the experience of emotion without going beyond the L1: all this is regulated, at a neurophysiological level, by the prefrontal cortex that controls the lexicon. What we will try to argue in this article is the way in which a lexical-enactive approach in teaching Spanish as FL can be very useful when acquiring lexical competence in a foreign language. L’objectif de cet article est de démontrer comment l’environnement est responsable de la construction du lexique dans l’acquisition d’une langue étrangère et, en particulier, de l’espagnol en tant que langue étrangère. Notre étude porte sur l’acquisition de l’espagnol par des apprenants italiens. Elle prend en considération l’existence, pour ces apprenants, d’un système conceptuel unique, mais avec des ramifications pour l’acquisition d’une langue étrangère qui proviennent, non pas tant du système conceptuel directement, mais de la L1. Nous, qui ne sommes pas des locuteurs natifs, pouvons entrer en contact avec notre lexique grâce à l’expérience que nous avons eue avec la L1. Quiconque apprend une L2, surtout à un niveau A1-A2, cherche des expressions dans sa L1 pour les traduire dans la L2 par le biais de leur construction mentale, tandis qu’un natif extraira l’information directement, concrétisant l’expérience de l’émotion sans aller au-delà de la L1 : tout cela est régulé, à un niveau neurophysiologique, par le cortex préfrontal qui contrôle le lexique. Dans cet article, nous tenterons de démontrer qu’une approche lexico-active dans l’enseignement de l’espagnol langue étrangère peut s’avérer très utile pour l’acquisition de compétences lexicales dans une langue étrangère.